Retrospective analysis of high-performance liquid chromatography screening for hemoglobinopathies among candidates undergoing initial medical evaluation at an Indian armed forces boarding center - Smita Rani Borgohain; Debajit Talukdar; Jitu Kalita (Indian Journal of Aerospace Medicine, 2026)
Objectives: Thalassemia is a hemoglobinopathy affecting the structure of the hemoglobin (Hb) molecule, and it, along with other structural hemoglobinopathies, is a group of genetic disorders causing abnormal production or structural abnormalities in the Hb molecule. Their prevalence is recorded in various global regions as well as in India. Candidates reporting for medical examination before selection in the Armed Forces are screened for hemoglobinopathies, and if evidence of hemoglobinopathies is seen using high-performance liquid chromatography (HPLC), the candidates are considered unfit for service as such individuals cannot be deployed at high altitude. The objective of the study is to determine the prevalence of hemoglobinopathies among asymptomatic healthy Air Force Common Admission Test/National Defence Academy/Combined Defence Services (AFCAT/NDA/CDS) candidates. Material and Methods: The subjects were both male and female AFCAT/NDA/CDS candidates in the age group 18–25 years. All candidates with or without microcytic hypochromic indices of anemia were screened for hemoglobinopathies, especially beta-thalassemia trait. Hb profiling was conducted with the Bio-Rad D-10 dual program which was employed for Hb analysis of our samples (extended Hb A2/F/A1c). Findings of the study were analyzed with a suitable statistical method. Results: The study population consisted of 680 individuals incorporated into the study for over 13 months from July 2022 to July 2023. Among them, 448 (65.88%) were males and 232 (34.11%) were females. Out of the 680 individuals tested by HPLC, 27 individuals (3.97%) were positive for hemoglobinopathies (18 were males and 09 were females). Hemoglobinopathies identified in our study were beta-thalassemia trait, HbE, HbD (Punjab), and HbS. Out of 3.97% hemoglobinopathies, beta-thalassemia trait was 2.5%, and HbE trait was 0.7% in the study population. Less common hemoglobinopathies were also identified in our study, such as HbD (Punjab) at 0.59% and HbS at 0.15%. Conclusion: The study gives us an insight into the comprehensive prevalence figures for hemoglobinopathies in a seemingly normal cohort group of Armed Forces candidates as well as reiterates that HPLC is a gold standard to help weed out individuals with abnormal hemoglobin. This will immensely benefit the organization and the Government exchequer by avoiding financial and manpower loss incurred in the training of unfit candidates.